Improvement in Opto-Electrical Properties of GaN MSM Photodetector by Contact Work-Function Selection - Ariff, F. A.; Zainal, N.; Hassan, Z. (2016)
Overall , this work evaluates the role of different metal contacts in improving electrical properties of GaN MSM (metal-semiconductor-metal) photodetector. The metal contacts were investigated in this work are AI , In, Pt. ITO and ZnO. Prior to the metalization , GaN layer was deposited on m-plane sapphire (AI203) substrate using electron beam (e-beam) evaporator, followed by ammonia annealing treatment to improve 111 -V stoichiometric balance. Subsequently , a metal mask consisting of two terminals, each with 3 inter-digitized fingers was aligned over -9 mm2 of the GaN samples. Contacts on each MSM photodetector were deposited by either RF/DC sputtering. Next each GaN MSM photodetector were annealed at 400 °C for 10 minutes in ambient air to diffuse the metal contact layer into th e GaN layer. The bes t spectral response of th e GaN MSM was observed at -360 nm GaN MSM photodetector with Pt contact shows a Schottky IV curve due to the large contact work -function . On the other hand. ohmic IV curve was observed on the remain ing GaN MSM photodetector IV measurement under dark and illuminated conditions shows a gain of -34 times between bias voltage or 1.5 V to 5.0 V. Responsivity measurement under pulsing UV light illumination was conducted to investigate the rise and fall time for each GaN MSM photodetector.